Influence of different brine water salinity on mechanical properties of fly ash-based geopolymer cement - Ridha, S. (Emerald Group Publishing Ltd., 2018)
Purpose: The purpose of this paper is to investigate the mechanical properties changing of geopolymer cement under different brine salinity. Design/methodology/approach: Geopolymer Cement of Class F Fly Ash and Class G Cement slurries were prepared according to API RP 10B. The optimum alkaline activator/cement and water/cement ratio of 0.44 was used for geopolymer and Class G cement samples, respectively. The alkaline activator was prepared by mixing the proportion of Sodium Hydroxide (NaOH) solutions of 8 M and Sodium Silicate (Na2SiO3) using ratio of 1:2.5 by weight. The slurries were cured for 24 hours at 130oC and 3,000 psi in HPHT Curing Chamber followed by coring process. Both cement sample were immersed in brine water salinity up to 28 days with different brine salinity up to 30 per cent of NaCl. The mechanical properties were investigated using OYO Sonic Viewer-SX and Uniaxial Compressive Strength. The surfaces of the cement samples were extracted for Scanning Electron Microscope (SEM) and EDS tests to evaluate the morphology and chemical compositions of the cured samples. Findings: The paper shows that geopolymer samples experiences strength reduction in brine water but the reduction rate of geopolymer is about half of the Ordinary Portland cement based oil well cement. The finding was also verified by SEM and EDS result. Originality/value: This paper investigates the mechanical property changes of emerging geopolymer cement due to different water salinity. The results provide potential application of geopolymer cement for oil well cementing. Â© 2018, Emerald Publishing Limited.